Hak Asasi Manusia Mantan Narapidana Korupsi dalam Peraturan Komisi Pemilihan Umum Nomor 20 Tahun 2018 Perspektif Maqashid Syariah Jasser Auda - Fathor Rahman; Muhammad Saiful Anam (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2020)
This article aims to discussing the conception of ex-corruption convicts human rights according to the General Election Commission Regulation No. 20 of 2018 systematically; regarding the concept of human rights and the explicit human rights of former corruption convicts in the General Election Commission Regulation No. 20 of 2018 in the perspective of Jasser Auda's Islamic maqashid concept.This research is qualitative research with a literature review. The perspective in this discussion is the concept of maqashid sharia Jasser Auda which uses a systems approach in Islamic law. The results shows that: 1) the current state of mind of the Indonesian people cannot be separated from contemporary issues regarding human rights, democracy, the nation state, the rule of law, and the ideals of progress and national prosperity in the national context; 2) PKPU Number 20 of 2018 is in line with maqashid al-sharia with a systems approach; 3) the prohibition of former corruption convicts from running for legislative elections is justified in the perspective of maqashid al-sharia Jasser Auda, in his avoidance with various dimensions, namely the social dimension, the bureaucratic dimension to achieve good governance, the political education dimension, the state philosophy dimension and justice.